When Pentecostals Cry : A Phenomenological Study of Encountering God - Warnelid, Martin, (Journal of Pentecostal Theology Supplement Series ;, 2026)
In When Pentecostals Cry, Martin Warnelid presents a unique perspective on the affective dimension of pentecostal spirituality by exploring fourteen narratives of encountering God by ordinary pentecostal believers. From a practical-theological perspective, the author creatively interprets the research findings through the leitmotif of pentecostal tears, engaging constructively with Hartmut Rosa's theory of resonance and Simeon Zahl's pneumatology. In doing this, the book offers a fresh understanding of what occurs when pentecostals cry that goes beyond dismissing the phenomenon as religious emotionalism. For the first time, affective experiences of encountering God are in this book interpreted as pneumatological resonance, a concept that expands the conversation on pentecostal spirituality in significant ways.